Therapeutic effects of rosehip fruit types in traditional and modern medicine (Iranian Society of Pharmacognosy, 2017)
Background and objectives: The genus Rosa is one of the most widespread members of Rosaceae family with more than 100 species. Rosa fruit (rosehip) has a long history of traditional uses in Islamic traditional medicine. It has been used for the treatment of several illnesses including ear, nose and throat problems, nausea and vomiting, headache and brain spasms. Beside the traditional uses, it has exhibited various pharmacological properties. To extend our view towards future indication of this fruit for medicinal and clinical purposes, this study was an attempt to review traditional applications, clinical properties, and pharmacological potentials of rosehip in various ethnomedical systems. Methods: Major ITM books were explored to find the main clinical uses of rosehip. Also to find pharmacological activities of rosehip, we searched some electronic databases such as PubMed and Scopus. Results: Several in vitro and in vivo pharmacological studies and clinical trials have confirmed the traditional uses of rosehip including neuroprotective activities. These studies have also suggested new properties such as anti-cancer, anti-rheumatoid arthritis, anti-diabetic, antihyperlipidemic activities and gastroprotective effects. Conclusion: Systems of traditional medicine plays an important role in discovering new drugs.